Allometry indicates giant eyes of giant squid are not exceptional - Schmitz, Lars (BioMed Central, 2013)
BACKGROUND: The eyes of giant and colossal squid are among the largest eyes in the history of life. It was recently proposed that sperm whale predation is the main driver of eye size evolution in giant squid, on the basis of an optical model that suggested optimal performance in detecting large luminous visual targets such as whales in the deep sea. However, it is poorly understood how the eye size of giant and colossal squid compares to that of other aquatic organisms when scaling effects are considered. RESULTS: We performed a large-scale comparative study that included 87 squid species and 237 species of acanthomorph fish. While squid have larger eyes than most acanthomorphs, a comparison of relative eye size among squid suggests that giant and colossal squid do not have unusually large eyes. After revising constants used in a previous model we found that large eyes perform equally well in detecting point targets and large luminous targets in the deep sea. CONCLUSIONS: The eyes of giant and colossal squid do not appear exceptionally large when allometric effects are considered. It is probable that the giant eyes of giant squid result from a phylogenetically conserved developmental pattern manifested in very large animals. Whatever the cause of large eyes, they appear to have several advantages for vision in the reduced light of the deep mesopelagic zone.